1986
DOI: 10.1002/arch.940030404
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Δ5,7 ‐ and Δ8‐sterols by larvae of Heliothis zea

Abstract: Larvae from two populations of Heliothis zea were reared on artificial diets containing various sterols, which supported suboptimal growth, and their tissue sterols were characterized in order to determine how these dietary sterols are utilized by this insect. The sterols studied included A5r7-sterols (7-dehydrocholesterol or ergosterol), A8-sterols (lanosterol andlor 2Cdihydro-lanosterol), and a A5-sterol (4,4-dimethylcholesterol). Although larvae did not develop on 4,4dimethylcholesterol, those fed primarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
1

Year Published

1988
1988
1997
1997

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 8 publications
(15 reference statements)
1
16
1
Order By: Relevance
“…The corn earworm can tolerate certain modifications in the nucleus, as shown earlier by Ritter (8)(9)(10), studying a series of ∆ 0 -, ∆ 5 -, and ∆ 7 -, and ∆ 8 -sterols. However, we found that many phytosterols that are transformed naturally by plants, such as those with a 4,4-dimethyl group (24-dihydrolanosterol, lanosterol, and cycloartenol), a 9β,19-cyclopropane Structures of sterols are reported in Figure 2.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…The corn earworm can tolerate certain modifications in the nucleus, as shown earlier by Ritter (8)(9)(10), studying a series of ∆ 0 -, ∆ 5 -, and ∆ 7 -, and ∆ 8 -sterols. However, we found that many phytosterols that are transformed naturally by plants, such as those with a 4,4-dimethyl group (24-dihydrolanosterol, lanosterol, and cycloartenol), a 9β,19-cyclopropane Structures of sterols are reported in Figure 2.…”
Section: Resultsmentioning
confidence: 68%
“…When cholesterol is not available and the dietary phytosterol cannot undergo metabolism to cholesterol by the insect, then the nutritional sterol is nonutilizable and larval death should ensue. Ritter (7)(8)(9)(10), studying sterol structure-activity relationships in H. zea, has shown that the type and amount of sterol available to the insect diet influence growth and development. In our comparative studies on metabolism of 4-desmethyl, 4-monomethyl and 4,4-dimethyl sterols fed to Manduca sexta, we found that sterol utilization was associated with the level of phytosterol in the medium preparation and the degree of sterol metabolism by the insect (11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been shown in H . zea that the percentage of esterification of sitosterol and stigmasterol was much smaller than that of cholesterol and other C-27 sterols [7]. 2.…”
Section: Discussionmentioning
confidence: 97%